Efeito do tamanho do vaso e do número de plantas por vaso sobre a produção de massa vegetal em experimento de estufa - Ferreira de Novais , Roberto; Mário Braga, José (Revista Ceres, 2025)
The objective of this experiment was to study the effect of pot size (0.5; 1.0 and 2.0 kg of soil) and the number of Italian millet plants per pot (5, 10 and 20) on the production of plant material and the statistical precision of an experiment conducted in the greenhouse.